Investigation of the radiation characteristics of the antenna based on a magnetized gyromagnetic resonator with different types of emitters in the form of three-dimensional resonators of different designs - L.D. Lozhkin; A.A. Soldatov; A.A. Voronoy; S.Yu. Sitnikov (Физика волновых процессов и радиотехнические системы, 2019)
In this paper we consider the antenna based on the magnetic gyromagnetic resonator with different types of bulk resonators. The magnetized gyromagnetic resonator is excited through the feeder line by the microwave field and then, in turn, excites the volumetric resonator or the reactor antenna, which radiate an electromagnetic field of rotating polarization into space. Such emitters have a number of unique properties that are provided by the magnetic gyromagnetic resonator: radiation of the circular polarization field; electrical switching of the direction of rotation, high frequency selection and magnetic tuning of the central frequency of radiation. Changing the direction of rotation of the field vector occurs by switching the current in the electromagnet. The shift of the central frequency of radiation can be made by changing the current in the field coil with a wire. In the axial direction, the ellipticity coefficient of the radiation field is close to one. Five types of volumetric resonators and a horn radiator are experimentally investigated. The characteristics of the radiation of the investigated resonators are compared.